REVOLUSI ILMIAH THOMAS KUHN: PERUBAHAN PARADIGMA DAN IMPLIKASI DALAM BANGUNAN ILMU KEISLAMAN - Rahmat Effendi (Universitas Islam Negeri Imam Bonjol Padang, 2020)
a lot of knowledge that produces a variety of technologies that can be used by humans. The value of truth is measured to what extent it can be observed through various researches in the scientific method. Profane science must be born systematically and methodically. The results of such paradigms give rise to anomalies among scientists and scientists. Faced with that there is an idea to build new science so as not to glorify a scientific method. This idea was sparked by the great scientist Thomas Kuhn. For him, there must be a revolution in the structure of modern science. Changing the old paradigm to the new paradigm must be done following the times (up to date). Furthermore, the building of science that has been built firmly in the West has been eroded by moral values and spirituality. What and how it relates to the building of Islamic science is a challenge for Muslims in taking the meaning of the scientific revolution. A paradigm shift is needed in every dimension of science. The focus of this research is Thomas Kuhn's scientific revolution which then drew the common thread over the building of Islamic science. This research is based on library research to reveal how modern science works and its relation to Islamic science.